(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the highest level of the hierarchy of management, covering both daily management and the burden of responsibility for it, or rather the idea of a person, society, community in most cases of life and activity, each of which represents a separate but interrelated aspect, a step.